Maintenir l’espace de production de petite taille en ville : le cas des entreprises de construction bruxelloises (1965-2016) - Sarah De Boeck; Matthijs Degraeve; Frederik Vandyck (Brussels Studies, 2020)
While productive activities are high on the academic and political agenda of the Brussels-Capital Region (BCR), small-scale production space is still rapidly disappearing. Based on a combination of quantitative and qualitative data, this article sketches a historical comparative perspective on the spatial organization of small and medium-sized construction companies in the BCR. It shows that in both 1965 and 2016 construction companies have a scattered distribution pattern over the Region's built-up area, that they follow the Region's built-up expansions and that they have a strong path dependence. The interviewed entrepreneurs, mainly focused on renovation, are locally anchored and work mainly with local customers, employees and suppliers. Although the construction companies' central location and local anchoring offer an important added value to the BCR, their presence is under pressure and, due to their small-scale organization, they often stay invisible to the authorities. In order to continue to guarantee small-scale economic activities such as the construction sector in the city, this article argues for a spatial policy that provides affordable and centrally located production space.